REHABILITASI NARAPIDANA DALAM OVERCROWDED LEMBAGA PEMASYARAKATAN (REHABILITATION OF PRISONERS IN OVERCROWDED CORRECTIONAL INSTITUTION) - Lidya Suryani Widayati (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2012)
Imprisonment based on the idea of the correctional system oriented rehabilitation for prisoners with the goal of returning prisoners to society. However, the concept of rehabilitation facing obstacles due to the overcrowded in the correctional institution. The more overcrowded, the greater the potential for conflict that a correctional officer will be more focused on the safety factor than the rehabilitation factor. Overcrowded also affect the state budget because the cost of meals for the prisoners to be increased. Facilities and infrastructure are already very low, for rehabilitation becomes increasingly minimum, because the funds are concentrated on tackling meal to prisoners. One of the factors that influence the occurrence of overcrowded is the number of judges who sentenced imprisonment. Therefore, to overcome the problem of overcrowded that directly affect the rehabilitation of prisoners to do in the early stages when deciding on the verdict. Apart from having to consider the goals and guidelines of sentencing the judge is not expected to impose imprisonment if he thinks more appropriate prisoners to get out of prison rehabilitation. Rehabilitation of prisoners both inside and outside the correctional institution should be supported by professional staff, facilities and adequate budget. Apart from the state budget, the budget for the needs of the correctional institution can be obtained from the development potential and at the same prison as a way for prisoners to develop their skills and talents.ABSTRAKPidana penjara dengan sistem pemasyarakatan lebih berorientasi pada ide pembinaan (rehabilitasi) terhadap narapidana dengan tujuan untuk mengembalikan lagi narapidana ke masyarakat. Namun konsep rehabilitasi menghadapi kendala overcrowded Lembaga Pemasyarakatan (LP). Semakin overcrowded LP maka semakin besar potensi konflik sehingga petugas LP akan lebih memusatkan perhatiannya pada faktor keamanan daripada faktor rehabilitasi narapidana. Overcrowded juga mempengaruhi anggaran negara karena biaya makan penghuni menjadi meningkat. Sarana dan prasarana yang sudah sangat minim untuk melaksanakan rehabilitasi menjadi semakin minim, karena dana terkonsentrasi untuk menanggulangi makan narapidana. Salah satu faktor yang mempengaruhi terjadinya overcrowded LP adalah banyaknya hakim yang menjatuhkan vonis pidana penjara. Oleh karena itu, untuk mengatasi masalah overcrowded yang berpengaruh langsung terhadap rehabilitasi narapidana dapat dilakukan di tahap awal pada saat penentuan vonis hakim. Selain harus mempertimbangkan tujuan dan pedoman pemidanaan maka hakim diharapkan tidak menjatuhkan pidana penjara apabila menurutnya narapidana lebih tepat mendapatkan rehabilitasi di luar LP. Rehabilitasi narapidana baik di dalam maupun di luar LP harus didukung dengan profesionalisme petugas, sarana prasarana dan anggaran yang memadai. Selain dari anggaran negara, anggaran untuk kebutuhan LP dapat diperoleh dari pengembangan potensi pemasyarakatan dan sekaligus sebagai jalan bagi narapidana untuk mengembangkan ketrampilan dan bakatnya.